Otok. - Beskid, V.; Cvetnic, Sanja; Grzinic, Marina; Kafka, Ivan; Kovac, Leonida; Maracic, Antun; Popovcak, Borivoj; Shanks, Janet; Tolj, Slaven; Turkovic, Evelina; Vukmir, Janka; Soros Center for Contemporary Arts, Zagreb; et al. (Zagreb : Soros Center for Contemporary Arts, 1996)
Kozaric, Ivan ; Schubert, Edita ; Marcic, Antun ; Roncevic, Igor ; Cvjetanovic, Boris ; Efendic, Rino ; Jandric, Dorde ; Petercol, Goran ; Juric, Duje ; Savic-Gecan, Tomo ; Kopljar, Zlatko ; Stacho, L'ubo ; Shanks, Janet ; Smid, Aina ; Grzinic, Marina ; Kafka, Ivan ; Bace, Josip ; Gril, Marin ; Jelavic, Ivana ; Jurjevic, Bozidar ; Kraskovic, Denis ; Mitrovic, Marojica ; Pokas, Vesna
biografie
Engels
Kroatisch
2 volumes: catalogus + symposium Otok Island
Otok Island, Art Workshop Lazareti Dubrovnik / Soros Center for Contemporary Arts, Zagreb, 24.8. - 10.9.1996
boek
Keywords: Kroatië